Studi Pemikiran Hadis Nizar Ali: Hadist Versus Sains Memahami Hadist Musykil - Lujeng Lutfiyah, Muhammad Aly Mahmudi, Moh. Sahlul Khuluq (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
In Islam in addition to the Qur'an, hadith is an interesting thing to study and explore the elements of knowledge that exist in it. During this time the study of new hadiths dwelled on sanad and matan, even in the conservative realm without alignment with the world of science knowledge. Nizar ali tried to break the study to dare to judge the hadith from a scientific perspective. In this paper try to dig first: contemplation of hadith in the world of science. Second: nizar ali's thoughts in addressing hadith in the perspective of science. So that it can be found in the study of the value of science in the prophet's hadith and paradigama built in responding to hadith with science.